Counseling Students Perceptions of Applying Creative Techniques in Counseling Work - Sarhan, Wafa’ Younes; Banat, Suhaila Mahmoud; Al-Shatarat, Walid Mohammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the counseling students’ perceptions of applying creative techniques in counseling work. The study sample consisted of (300) male and female counseling students at Jordanian Universities. The researchers developed a scale to measure the counseling students’ perceptions of applying creative techniques in counseling work. The validity and stability of the scale were computed. The study results indicated that the level of students’ perceptions was high and there were significant differences in favor of females in the level of these perceptions. The results also revealed that there were no significant differences in the level of applying creative techniques in counseling work related to variables of qualifications, desire of the major, and their average. In light of the study results the researchers recommended to apply more surveys, experimental and qualitative studies about creative techniques and their applying.